180 FDA Trial of Decompression and Dynamic Sagittal Tether for Degenerative Spondylolisthesis: 24-Months Clinical and Radiographic Follow-Up. (April 2023) - Kim, Kee Duk; Sasso, FAANS; Rick; Hu, Serena; Bae, Hyun; Villavicencio, Alan T.; Lavelle, William F.; Yoon, Tim; Sandhu, Harvinder S.; Perez-Cruet, Mick J.; Bains, FAANS; Ravi; Kuo, Calvin; Stauff, Michael; et al.
Abstract : INTRODUCTION: Degenerative spondylolisthesis (DS) with lumbar spinal stenosis (LSS) is commonly treated with decompression and fusion. The LimiFlex Dynamic Sagittal Tether (DST) is an investigational stabilization device for patients with DS and LSS. METHODS: Patients with single-level Grade 1 DS with LSS were enrolled in FDA-IDE study (NCT03115983) comparing decompression with DST and decompression with TLIF. Clinical and radiographic outcomes were assessed at baseline through 24mo postop. All propensity score (PS) selected patients who had 24mo follow-up were included in this interim analysis. RESULTS: At 24 mo, 224 PS-selected patients (125DST/99TLIF) had clinical follow-up. Mean characteristics of DST/TLIF groups were: age 65.8/64.1 yrs; BMI 28.1/30.0; CCI 2.5/2.4; and 57.9%/70.1% female. Mean perioperative outcomes for DST/TLIF were: procedure time 112/187 min; EBL 52/240mL; LOS 0.6/2.9 d. Mean improvements at 24mo for the DST/TLIF groups were -58.0/-57.5 mm VAS-leg/hip, -48.3/-42.2 VAS-back and -40.0/-33.4 ODI with 91%/83% achieving 15pt ODI improvement. Within 24 months, 6.5% of DST and 7.6% of TLIF patients had additional surgery at the index or adjacent level. Radiographically, at 24mo, mean reductions for the DST/TLIF groups were -1.7°/-3.7° in flexion/extension ROM and -0.4 mm/-1.0 mm in dynamic translation. At baseline/24mo, the index segment accounted for 30%/27% of index+adjacent segments ROM in the DST group and 29%/12% in the TLIF group. CONCLUSIONS: These results suggest that decompression+DST stabilization for DS can achieve significant clinical improvement like fusion, without an increase in reoperations within 24 mo. Imaging demonstrated no increased instability in the DST group with maintained distribution of motion between the index+adjacent segments. Further follow-up should include PS-adjusted analysis of the study composite clinical success and longer follow-up to demonstrate clinical durability of this treatment.